2018
DOI: 10.1111/cdev.13150
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Academic Performance Across Compulsory Schooling and Thriving in Young Adulthood

Abstract: Thriving is a developmental process that is shaped by previous and current interactions within developmental contexts. We hypothesized that academic performance in the school context will positively predict thriving in young adulthood. Data of N = 2,043 students from Zurich were assessed with standardized tests in Grades 1, 3, 6, and 9. Results showed that a stronger increase in academic performance significantly predicted thriving at age 20, even after statistically controlling for various covariates. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 88 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…From a macro perspective, competence can be considered a fundamental need “to experience satisfaction in exercising and extending one's capabilities” (Levesque et al, 2004, p. 68) and its successful fulfilment is associated with intrinsic motivation, effective self‐regulation, positive social development and well‐being (Ryan & Deci, 2000). Following this reasoning, Tomasik et al (2019) have demonstrated that steeper educational gains across compulsory schooling predicted successful development as indicated by notions of competence, confidence in oneself, strong character, caring for others and positive connections with others (“Five Cs Model”; see Lerner et al, 2015). Notably, these constructs in turn are predictive for contribution to society (Lerner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…From a macro perspective, competence can be considered a fundamental need “to experience satisfaction in exercising and extending one's capabilities” (Levesque et al, 2004, p. 68) and its successful fulfilment is associated with intrinsic motivation, effective self‐regulation, positive social development and well‐being (Ryan & Deci, 2000). Following this reasoning, Tomasik et al (2019) have demonstrated that steeper educational gains across compulsory schooling predicted successful development as indicated by notions of competence, confidence in oneself, strong character, caring for others and positive connections with others (“Five Cs Model”; see Lerner et al, 2015). Notably, these constructs in turn are predictive for contribution to society (Lerner et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given the predictive association between academic performance at school and well-being in adulthood (Tomasik et al, 2019), it is important to investigate the impact of any cognitive training on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Intra‐individual variability in accuracy within and between sessions in working memory tasks has been associated with academic performance in 3rd and 4th grade school children (Dirk & Schmiedek, 2016 ), and a recent study in 6‐year‐old children showed that intra‐individual variability after working memory cognitive training was associated with performance in mathematics 3 years later (Judd et al., 2021 ). Given the predictive association between academic performance at school and well‐being in adulthood (Tomasik et al., 2019 ), it is important to investigate the impact of any cognitive training on academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…4There was a fifth survey on occupational outcomes (for more details, see Tomasik, Napolitano, & Moser, 2018), but this survey was not the focus of this study.…”
mentioning
confidence: 99%